Pattern recognition : 9th Mexican Conference, MCPR 2017, Huatulco, Mexico, June 21-24, 2017, Proceedings /: 9th Mexican Conference, MCPR 2017, Huatulco, Mexico, June 21-24, 2017, Proceedings. (2017) - Unknown
No abstract available